Molecular mechanisms related to bone damage in spinal tuberculosis revealed by 4D-label-free proteomics analysis - Xiao, Wenxuan; Yang, Guangling; Xu, Shuqin; Song, Shu; Tang, Yuting; Zhou, Tianyao; Huang, Weili; Zhang, Lu; Gu, Yutong (Frontiers in Cellular and Infection Microbiology, 2025)
AimsSpinal tuberculosis (STB) is a common form of extrapulmonary tuberculosis (ETB). However, the molecular mechanism of pathological injury in STB remains unclear. The purpose of this study was to explore the pathogenic mechanism of STB, and compare it with Escherichia coli (E.coli) bone infections and lumbar degenerative disease (LDD) patients.Main methodsIn this study, the infected lumbar spine bone tissue of STB patients was collected for the infection group. LDD patients and E.coli lumbar spine infection (SEcoli) patients were collected for the non-M.TB infection group. Proteins from the bone tissue were extracted for 4D-Label Free Proteomics (4D-LFQ) analysis to compare the pathogenesis and immune mechanisms of STB and SEcoli.Key findingsThe osteoclast growth inhibitory factors tumor necrosis factor receptor superfamily member 11B (TNFRSF11B) and semaphorin-3A (Sema3A) were significantly down-regulated in STB, while the protein Wnt-5a (WNT5A) secreted by osteoblasts was significantly up-regulated. These changes in STB bone metabolism may lead to an increase in the number of osteoclasts and bone injury. In addition, the significantly up-regulated expression of thymocyte selection-related family member 2 (THEMIS2) suggests that THEMIS2 may be a potential therapeutic target for STB that could control the Toll-like receptor response of macrophages. Meanwhile, the PI3K-Atk anti-apoptotic pathway and the ECM-receptor interaction pathway were inhibited during both infections.SignificanceThis study explored the pathogenic mechanism of STB based on proteomics and compared its differences with E.coli bone infection, providing new insight into the treatment of STB.